Effect of the mixture of Anacardium occidentale / Cocos nucifera oils in diesel on the corrosion rate of carbon steel in saline - Marín-Velásquez, Tomás Darío (2020)
In the research, the effect of mixtures of Anacardium occidentale oil and Cocos nucifera diluted in diesel oil was evaluated, as an anticorrosive coating applied to carbon steel, in saline solution. Pieces of carbon steel bars used as reinforcements in construction were used, which were treated with a 50:50 mixture of the oils, diluted in concentrations of 10, 20, 30 and 50% in diesel. The steel pieces were immersed in a 10% NaCl saline solution for 360 days at a constant temperature of 50 ° C. In addition, a control sample without treatment was also subjected to the saline medium and another sample treated only with diesel oil. Three replications were made per treatment and the results of corrosion rate by weight loss were analyzed, by Kruskal-Wallis nonparametric variance analysis, with the statistical program Statgraphics Centurion XVI.I. The treatments with oil blends in diesel, achieved the reduction of the corrosion rate with efficiencies between 96.59 and 98.30%, with statistically significant results, where the 50% blend stands out with significant difference compared to the others with 95% level of trust.